Algorithm of measuring signal processing in vector analyzers of circuits - A. A. Kopshaj; A. V. Gusinskij; A. V. Voroshen'; D. A. Kondrashov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
To improve the accuracy of measuring the S-parameters of microwave devices using vector network analyzers, it is proposed to use a digital processing algorithm based on the quadrature decomposition of the measurement signal followed by accumulation during the entire observation period. The article presents the results of mathematical modeling of the algorithm, as well as the results of the algorithm in a vector network analyzer of heterodyne type P4-mvm-118.